1995
DOI: 10.1128/jb.177.9.2505-2512.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification from Fusobacterium mortiferum ATCC 25557 of a 6-phosphoryl-O-alpha-D-glucopyranosyl:6-phosphoglucohydrolase that hydrolyzes maltose 6-phosphate and related phospho-alpha-D-glucosides

Abstract: 6-Phosphoryl-O-␣-D-glucopyranosyl:6-phosphoglucohydrolase (6-phospho-␣-glucosidase) has been purified from Fusobacterium mortiferum ATCC 25557. p-Nitrophenyl-␣-D-glucopyranoside 6-phosphate (pNP␣Glc6P) served as the chromogenic substrate for detection and assay of enzyme activity. The O 2 -sensitive, metaldependent phospho-␣-glucosidase was stabilized during purification by inclusion of dithiothreitol and Mn 2؉ ion in chromatography buffers. Various 6-phosphoryl-O-␣-linked glucosides, including maltose 6-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 49 publications
2
75
0
Order By: Relevance
“…In contrast to other species, F. mortiferum ferments an extraordinarily wide variety of carbohydrates (Robrish et al, 1991). Previously, in studies of maltose metabolism in F. mortiferum, we cloned and expressed a gene (malH) whose deduced sequence exhibits " 75 % residue identity with the phospho-α-glucosidase of K. pneumoniae (Thompson et al, 1995 ;Bouma et al, 1997). In the present report, we show that the gene adjacent to malH (designated malB) also encodes a putative EII(CB) protein that is " 60 % identical with AglA of K. pneumoniae.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In contrast to other species, F. mortiferum ferments an extraordinarily wide variety of carbohydrates (Robrish et al, 1991). Previously, in studies of maltose metabolism in F. mortiferum, we cloned and expressed a gene (malH) whose deduced sequence exhibits " 75 % residue identity with the phospho-α-glucosidase of K. pneumoniae (Thompson et al, 1995 ;Bouma et al, 1997). In the present report, we show that the gene adjacent to malH (designated malB) also encodes a putative EII(CB) protein that is " 60 % identical with AglA of K. pneumoniae.…”
Section: Introductionmentioning
confidence: 76%
“…Presently, F. mortiferum and K. pneumoniae are the only organisms known to ferment the five α--glucosyl--fructoses. Earlier we showed that MalH from F. mortiferum hydrolysed maltose 6h-phosphate (Thompson et al, 1995), and now we provide evidence for the cleavage of the phosphorylated isomers of sucrose by this enzyme. The phospho-α-glucosidase gene (malH) is adjacent to the gene malB, whose now completed sequence predicts a polypeptide that in size, domain structure, and conserved motifs (GITE and CATRLR) is characteristic of an EII(CB) transporter of the PEP : PTS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 two genes for which the deduced open reading frames exhibited extensive homology with an NAD ϩ and metal-dependent GHF4 phospho-␣-glucosidase that we had found in several bacterial species, including Bacillus subtilis (14), Fusobacterium mortiferum (13,23,24), and Klebsiella pneumoniae (15). For purposes of distinction, we refer to the two putative phospho-␣-glucosidases in C. acetobutylicum 824 as MalH (maltose 6-phosphate hydrolase) and PagL (phospho-␣-glucosidase), respectively.…”
mentioning
confidence: 99%